Syriac churches encountering Islam (Piscataway, NJ)
xii, 253 sayfa
Keywords: “The present volume includes the papers of the first PRO ORIENTE Colloquium Syriacum, which took place in Salzburg, Austria and concentrated on the Syriac Churches’ experiences with Islam. The papers in this volume survey the whole history of these two communities from the times of the Four Caliphs through the Umayyad, Abbasid, and Ottoman periods. Topics include the personal status of Christians under Islam, the ecclesiastical response to the rise of Islam, the Indian experience and the present situation“ -- Yayıncı.